2005
DOI: 10.1002/ejoc.200500166
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Suzuki Coupling with Terminal Alkynes – Application to the Synthesis of 2,3‐Disubstituted Benzo[b]furans

Abstract: The Suzuki coupling reaction between alkynylboronic esters (generated in situ from acetylenic derivatives) and aryl bromides, pyridyl bromides or vinyl bromides is reported. 5-endo-dig-iodocyclisation of o-alkynylanisoles, generated by this palladium-catalyzed Suzuki coupling reaction, was performed with N-iodosuccinimide (NIS) in the presence of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(19 citation statements)
references
References 33 publications
(18 reference statements)
0
19
0
Order By: Relevance
“…Suzuki couplings of potassium alkyl-, aryl-, alkynyl-, and alkenyltrifluoroborates [23,[257][258][259][260][261][262], potassium triethyl 2-indolylborate [263], and lithium alkynyltriisopropoxyborates [264] were described. Alkenyl tellurides were coupled with alkynyltrifluoroborates [265].…”
Section: Carbon-carbon Bond-forming Reactions Via Transmetallationmentioning
confidence: 99%
“…Suzuki couplings of potassium alkyl-, aryl-, alkynyl-, and alkenyltrifluoroborates [23,[257][258][259][260][261][262], potassium triethyl 2-indolylborate [263], and lithium alkynyltriisopropoxyborates [264] were described. Alkenyl tellurides were coupled with alkynyltrifluoroborates [265].…”
Section: Carbon-carbon Bond-forming Reactions Via Transmetallationmentioning
confidence: 99%
“…17 Since then transition metal catalyzed coupling/ cyclization of suitably functionalized alkynes as starting materials has been focus for the synthesis of 2,3-diarylbenzofurans and 2,3-diarylnaphthofurans. [18][19][20][21] A number of methods have been developed for synthesis of 2,3-diarylbenzofurans but synthetic routes for naphthofurans are limited, 11,14 and synthesis of diversified naphthofurans still presents major challenge in organic synthesis.…”
Section: Figure 1 Structure Of Bioactive Benzofuran and Naphthofuransmentioning
confidence: 99%
“…Hence, we also sought to develop a simpler and more efficient method for the synthesis of the nitrobenzonitrile precursor and the authentic standard FPEB. Colobert et al recently reported a methodology of palladium-catalyzed Suzuki-like sp-sp2 coupling of aryl halides with terminal alkynes for the synthesis of 2,3-disubstituted benzo[ b ]furans, by first deprotonating the alkynes with n -butyl lithium to form an alkynyllithium and then reacting with triisopropylborate to generate a lithiated boronate complex in situ, followed by Pd-catalyzed coupling with arylbromides (Castanet et al, 2000; Colobert et al, 2005). We adopted this methodology for an efficient, one-pot preparation of FPEB and its nitrobenzonitrile radiolabeling precursor from commercially available building blocks.…”
Section: Introductionmentioning
confidence: 99%